Medical Management of the Transplant Patient: Long-term Follow-up - Massin, Edward K. (1987)
Of the 165 patients who have undergone cardiac transplantation at the Texas Heart Institute since 1982,(*) 159 long-term survivors have been followed up for an average of 1 year. Here I report on post-transplant complications in both the short and long terms, giving figures and treatment protocols where applicable. (Texas Heart Institute Journal 1987; 14: 262-267)